1998
DOI: 10.1046/j.1471-4159.1998.70020524.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Secretion of Alzheimer Amyloid Precursor Protein by the Mitogen‐Activated Protein Kinase Cascade

Abstract: Activation of protein kinase C (PKC) regulates the processing of Alzheimer amyloid precursor protein (APP) into its soluble form (sAPP) and amyloid β‐peptide (Aβ). However, little is known about the intermediate steps between PKC activation and modulation of APP metabolism. Using a specific inhibitor of mitogen‐activated protein (MAP) kinase kinase activation (PD 98059), as well as a dominant negative mutant of MAP kinase kinase, we show in various cell lines that stimulation of PKC by phorbol ester rapidly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 32 publications
5
73
1
Order By: Relevance
“…32 However, for the latter mechanism as it relates to APP metabolism, there are contrasting reports. Desdouit-Magnen et al 33 were not able to demonstrate a block of carbacholmediated sAPPa release in PC12-M1 cells treated with the MEK inhibitor PD98059. On the same cellular model, however, Haring et al 13 showed a significant inhibition of carbachol-mediated sAPPa release by PD98059.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…32 However, for the latter mechanism as it relates to APP metabolism, there are contrasting reports. Desdouit-Magnen et al 33 were not able to demonstrate a block of carbacholmediated sAPPa release in PC12-M1 cells treated with the MEK inhibitor PD98059. On the same cellular model, however, Haring et al 13 showed a significant inhibition of carbachol-mediated sAPPa release by PD98059.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, no differences in the activation of the MAP-kinase system were detected between SYa4 and SYwt cells, suggesting that the recruitment of ERKs was not affected by the specific downregulation of PKCa. This also suggests that although MAP kinases can be activated by PKC following phorbol ester treatment 33,34 and that such activation may promote sAPPa release, PKCa is not the kinase isoform involved. This is consistent with data in the literature that suggests that PKCe is the only kinase isoform in SK-N-BE2(C) neuroblastoma cells involved in MAP-kinase activation upon m3 muscarinic receptor challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the MAPK signaling pathway has recently been implicated in both PKC and tyrosine kinase receptor regulation of APP processing (45,46). We therefore assessed which, if any, of these kinases is involved in mediating the action of NSAIDs on sAPP␣ release using specific signaling inhibitors (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These include the protein kinases PKA, PKC, GSK3-␤, and Cdk5 (3,(30)(31)(32), and the protein phosphatases PP1/PP2A and PP2B (30,33). Early studies demonstrated that activation of PKA or PKC or inhibition of PP1/PP2A or PP2B causes a dramatic reduction in the formation of A␤ and/or an increase in the amount of the ␣-secretase cleavage product sAPP␣ (30).…”
Section: )mentioning
confidence: 99%